The factor inhibiting HIF regulates T cell differentiation and anti-tumour efficacy - Bargiela, David; Cunha, Pedro P.; Veliça, Pedro; Krause, Lena C. M.; Brice, Madara; Barbieri, Laura; Gojkovic, Milos; Foskolou, Iosifina P.; Rundqvist, Helene; Johnson, Randall S. (Frontiers in Immunology, 2024)
T cells must adapt to variations in tissue microenvironments; these adaptations include the degree of oxygen availability. The hypoxia-inducible factor (HIF) transcription factors control much of this adaptation, and thus regulate many aspects of T cell activation and function. The HIFs are in turn regulated by oxygen-dependent hydroxylases: both the prolyl hydroxylases (PHDs) which interact with the VHL tumour suppressor and control HIF turnover, and the asparaginyl hydroxylase known as the Factor inhibiting HIF (FIH), which modulates HIF transcriptional activity. To determine the role of this latter factor in T cell function, we generated T cell-specific FIH knockout mice. We found that FIH regulates T cell fate and function in a HIF-dependent manner and show that the effects of FIH activity occur predominantly at physiological oxygen concentrations. T cell-specific loss of FIH boosts T cell cytotoxicity, augments T cell expansion in vivo, and improves anti-tumour immunotherapy in mice. Specifically inhibiting FIH in T cells may therefore represent a promising strategy for cancer immunotherapy.